Learning While Preserving: The Effectiveness of Project-Based Recycling Learning - Vivi Yunita Sari; Vanda Rezania (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This study aims to examine the effectiveness of project-based learning in increasing environmental awareness of elementary school students. Through experimentation, students who participated in project-based learning were compared with a control group. The results showed that students in the experimental group experienced significant improvements in knowledge, positive attitudes, and recycling behavior compared to the control group. This finding indicates that project-based learning is not only effective in the transfer of knowledge about recycling, but also successfully fosters awareness of the importance of environmental conservation. This is in line with the concept of 'learning while preserving', where the learning process is integrated with real actions to protect the environment.